Temperature Inversion and Ultrafine Particulate/Near Ultrafine Particulate Matter Concentrations in the Salt Lake Valley - Mecate, Danielle; Handy, Rod; Pahler, Leon; Sleeth, Darrah; Ramsay, Joemy; Schaefer, Camie (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Ultrafine particulate (UFP) matter exposures are associated with negative health outcomes. UFPs (<100nm) and near UFP (NUFP) matter (4.5nm - 250nm) are trapped by the bowl-like geography of the Salt Lake Valley causing winter inversions (i.e., trapped particulate matter (PM)). Enmont PUFP C100 and Grimm 1.109 particle counters were used to define NUFP concentrations during inversion (n=5) and non-inversion (n=5) days at 7 sites. NUFP concentrations served as a proxy for the UFP fraction. NUFP concentrations were log-transformed and multivariable mixed effects linear regression models determined if NUFP concentration differed between inversion and non-inversion or by length of inversion. Difference in fraction NUFP was also analyzed. The mean NUFP concentration was 1.49-fold higher during inversions (95% CI 1.11–2.02), whereas the fraction declined by 0.22 (95% CI -0.31– -0.13). Increased NUFP concentrations during inversions may lead to increased adverse health outcomes. These findings have serious implications for inversion-prone regions.